Análisis de una polémica fundacional: inmigración, religión y desarrollo económico en la Asamblea Constituyente argentina de 1853 - Mónica Baretta (ALED, 2019)
From the beginning of the independent period, the leading classes of Argentina faced the need to populate the vast national territory, and the incorporation of foreign inhabitants was from an early date the undisputed solution to that problem. However, despite the broad consensus that existed on the issue, there were divergent points of view about the “type of immigration” that was desired. In this context, during the debates of the Constituent Assembly of 1853, the treatment of the article 14 of the National Constitution gave rise to an argumentation situation (Plantin 2012) that raised the immigration issue when discussing freedom of religion. Supporters and detractors of religious tolerance linked this issue more or less directly with the foreign population that, it was hoped, came to populate the Argentine territory.Thus, in this paper the arguments put into play in this controversy are analyzed, to point out, on the one hand, the polarization and incompatibility of the positions in dispute (Angenot 2008; Amossy 2016) and, on the other, the starting points that are common on both sides of the debate. In this sense, we are interested in investigating the way in which these arguments construct the image of the immigrant, while offering certain representations about the local population and the idea of economic development